The Role of People's Oral Creation in Increasing the Effectiveness of Teaching in Primary Education - Boltayeva Go‘Zal Talibovna (Genius Journals, 2023)
This article is scientifically based on the specifics of cultivating hard work in primary education through national values. The issue of educating the next generation on the basis of national values is also covered.
Keywords: folklore; labor education; moral culture; moral thinking